Predicting Sea Level Rise Using Artificial Intelligence: A Review - Bahari N.A.A.B.S.; Ahmed A.N.; Chong K.L.; Lai V.; Huang Y.F.; Koo C.H.; Ng J.L.; El-Shafie A. (Springer Science and Business Media B.V., 2024)
Forecasting sea level is critical for coastal structure building and port operations. There are, however, challenges in making these predictions, resulting from the complicated processes at various periods. This study discussed the continual development of the application and forecasting approaches for sea level rise, in standard and advanced modeling versions. To date, the tide gauge and satellite altimetry are the commonly used approaches for sea level measurement. Tide gauges are mostly deficient in typical offshore circumstances